ChemInform Abstract: Catalytic Carbon Insertion into the β‐Vinyl C—H Bond of Cyclic Enones with Alkyl Diazoacetates. Issue 32 (18th July 2013) - Lee, Sung Il; Kang, Byung Chul; Hwang, Geum‐Sook; Ryu, Do Hyun
Abstract A novel Lewis acid‐promoted Csp2‐H functionalization reaction of cyclic enones using various diazoacetates is described.